Athlete’s Entrepreneurship Interest A Review Of The Perspective Of Sportpreneur Program, Personality And Self-Efficacy - Utami, Christina Whidya; Padmalia, Metta; Sudyasjayanti, Christina; Ernantyo, Yosef Evandro (Universitas Ciputra Surabaya, 2021)
The effort in developing the economy and reducing unemployment in Indonesia is through entrepreneurship. In order to conduct business well, entrepreneurs need to be motivated by several factors in order to have the interest for entrepreneurship. Luthje and Franke’s model (LFM) argued that in order to spark the interest for entrepreneurship, it is affected by several factors, which are internal and external factor. Therefore, this goal of this research is to determine how big the impact of internal and external factor on interest for entrepreneurship. The aim of this research is to understand and analyze the effect of entrepreneurial education, consisting of Sportpreneur Program, personality and self-efficacy on interest for entrepreneurship. There are 4 variables in this study, which are: entrepreneurial education (X1), personality (X2), self-efficacy (X3) and entrepreneurship interest (Y). The research method used is quantitative method, whereby the data was obtained through online distribution of questionnaires. Research sample/ subject is East Java KONI athletes that have participated in sportpreneur program in Institusi Surabaya. Based on the result of this research, it is shown that entrepreneurship interest is positively and significantly affected by Entrepreneur education consisting of Sportpreneur progam and self-efficacy, however, entrepreneurship interest is not affected by personality.